A Line of Continuity in Jan Patocˇka’s Phenomenological Thought - Ortega Rodriguez, Iván (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Jan Patocˇka’s phenomenological thought is frequently characterised as having a clear discontinuity in its evolution. Thus, two distinct phases are differentiated. The first one is clearly subjectivist, following Husserl’s transcendental phenomenology, whereas the second is focused on the finite existent and «a-subjective» phenomenology. This description is undoubtedly true. However there are also elements that show a certain continuity between these two phases. The consideration of this basic continuity is essential for a better understanding of his phenomenological research as well as the ensemble of his thought.
Keywords: Patocˇka; phenomenology; contemporary philosophy